2022
DOI: 10.1021/acs.jafc.2c00147
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Related Diseases and Delivery Mode can Affect the Content of Human Milk Oligosaccharides: A Preliminary Study

Abstract: Human milk oligosaccharides (HMOs) are the second most abundant carbohydrates in colostrum. In this study, we performed a quantitative analysis of 13 oligosaccharides in 99 colostrum samples obtained from mothers living in Northwest China. The analysis combined liquid chromatography-mass spectrometry (LC-MS) with 2-amino-N-(2-aminoethyl)benzamide (AEAB) labeling and nonsecretors accounted for 17%. Compared with healthy secretor mothers, those with gestational diabetes mellitus presented lower levels of sialyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 58 publications
5
12
0
Order By: Relevance
“…Moreover, the authors did not classify the secretory phenotypes. Another research that explored the difference between GDM and healthy donors showed that the concentration of 3′-SL in colostrum of mothers in the secretor GDM group (n = 18) was significantly lower than that of mothers in the healthy group (n = 43) (GDM: 144 ± 161 mg/L versus healthy: 252 ± 181 mg/L, p < 0.05), which was the only individual HMO that differed between the two groups [ 31 ]. Moreover, not only was the 3′-SL content significantly lower in the GDM group than in the healthy group, but also the total sialylated HMOs content was lower than in the healthy group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the authors did not classify the secretory phenotypes. Another research that explored the difference between GDM and healthy donors showed that the concentration of 3′-SL in colostrum of mothers in the secretor GDM group (n = 18) was significantly lower than that of mothers in the healthy group (n = 43) (GDM: 144 ± 161 mg/L versus healthy: 252 ± 181 mg/L, p < 0.05), which was the only individual HMO that differed between the two groups [ 31 ]. Moreover, not only was the 3′-SL content significantly lower in the GDM group than in the healthy group, but also the total sialylated HMOs content was lower than in the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…Second, HMOs have been shown to affect intestinal flora, which have not been explored in our study. Third, the literature has shown that the content of HMOs is also affected by diet [ 31 ]. Considering the special situation of the GDM group (all the women with GDM controlled their blood sugar through diet and exercise according to the dietary recommendation), our study did not investigate the relationship between diet and HMOs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, it is only applicable to oligosaccharides with a defined structure and commercial standards, thereby excluding the quantification of total, neutral, and sialylated oligosaccharides. 22 The phenol-H 2 SO 4 method is mainly used for the determination of oligosaccharides or polysaccharides, and this method is relatively stable and repeatable. 21 But oligosaccharides in milk contain a lot of sialic acid-modified oligosaccharides, sialic acid is a nine-carbon sugar without aldehyde group, which can not develop color in phenol−sulfuric acid system.…”
Section: Introductionmentioning
confidence: 99%
“…Oligosaccharide content is determined by high-performance liquid chromatography (HPLC), the phenol-H 2 SO 4 method, and the resorcinol-HCl method. HPLC requires specific internal oligosaccharide standards to allow for absolute quantification. As a result, it is only applicable to oligosaccharides with a defined structure and commercial standards, thereby excluding the quantification of total, neutral, and sialylated oligosaccharides . The phenol-H 2 SO 4 method is mainly used for the determination of oligosaccharides or polysaccharides, and this method is relatively stable and repeatable .…”
Section: Introductionmentioning
confidence: 99%